دراسة تحليلية طيفية لتحسين شروط تحديد عنصر الزنك باستخدام الكاشفBPT وتطبيقها على بعض الصخور السورية - معروف, محمد; حلاق, حمزة (Latakia University Journal -Basic Sciences Series, 2017)
تم في هذا البحث تحسين شروط تحديد الزنك الثنائي في الصخور السورية الساحلية في منطقة الباير والبسيط شمال اللاذقية باستخدام طريقة التحليل الطيفي الضوئي بالاعتماد على تشكيل معقد مع BPTعند الطول الموجي (430nm) من خلال دراسة تأثير درجاتpH الوسط, وتأثير التداخل الناتج عن وجود بعض الأيونات:النيكل, والحديد الثنائي, والكالسيوم، والنحاس، والكروم, والمنغنيز التي تعيق عملية تحديد الزنك بوساطة الكاشف BPT والتي اختلفت نسب إعاقتها وفق التسلسل الآتي: Mn2+>Cr3+<Cu2+< Fe 2+< Ca2+<Ni2. بينت نتائج الدراسة أن قيمة pH الوسط المثلى لهذا التحديد هي (pH=5), وأن مجال التركيز الذي تتحقق عنده العلاقة الخطية حسب قانون بيير- لامبرت هو6 0.1-6µg/ml؛ إذ تم التأكد من دقة التحليل باستخدام فلورة أشعة- X وحسب التقارب بين دقتي الطريقتين باستخدام معامل فيشرإذ بلغ حد الكشف عن الزنكµg/ml 0.015.In this research improve the conditions determining zinc(II) using the method of optical spectroscopy based on the formation of a complex with BPT when the wavelength (430nm) and through the study of the impact of degrees pH the middle, and the effect of the interference caused by the presence of some of the nickel ions, iron(II) , calcium, copper, chromium, and manganese that hinder the process of identifying zinc-mediated this reagent .BPT results of the study showed that the optimum pH value in the middle of this selection is (pH = 5) and that the focus area that has achieved linear relationship according to the law of Pierre Lambert is 0.1-6 μg/ml, Been confirmed the accuracy of the analysis using x-ray fluorescence and then by the rapprochement between the two methods using Dgueta Fisher coefficient, amounting to detection limited of zinc was 0.015μg / ml